Vitamin D deficiency in dengue fever patients' coinfected with H. pylori in Pakistan. A case-control study - Mirza, Wajid Ameen; Zhang, Ke; Zhang, Rongguang; Duan, Guangcai; Khan, Muhammad Shahid Nawaz; Ni, Peng (Frontiers in Public Health, 2022)
Introduction; Dengue fever is a vector borne disease with an estimate of 390 million persons getting the infection each year with a significant public health impact. In this case control study we explored the vitamin D deficiency in dengue fever patients with helicobacter pylori infection with dengue negative controls with Helicobacter pylori infection. We have also assessed the co-relation between vitamin D levels and its effect on warning signs of the dengue fever. Further we have investigated whether infection with Helicobacter pylori has any effect on warning signs of the dengue fever patients, and the vitamin D deficiency in all serotypes of the dengue virus infected patients. Methods; this case control study compared the hospitalized dengue fever patients with Helicobacter pylori infection with dengue negative controls with Helicobacter pylori infection. The association of the vitamin D levels with age, gender and Helicobacter pylori infection in dengue fever patients was assessed using chi square and multivariate logistic regression analysis. Results; four hundred dengue fever patients with Helicobacter pylori infection were compared with four hundred dengue negative controls with helicobacter pylori infection. Mean (SD) age was 29.96 (10.5) and 29.88 (10.7) years among cases and controls, respectively. Most of the dengue fever patients with Helicobacter pylori infection were deficient in vitamin D while compare with dengue negative controls with Helicobacter pylori infection. In multivariate logistic regression, the dengue cases with Helicobacter pylori infection were .056 times (95% CI: .024, .128, P= .000) more likely to have vitamin D ‘deficiency’, while compared with the cases who did not have Helicobacter pylori infection. Conclusion; The present study proposes that vitamin D deficiency in dengue fever patients co-infected with Helicobacter pylori is much higher than the dengue fever negative controls infected with Helicobacter pylori.